2002
DOI: 10.1097/00005344-200205000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and Acute Effects of Dronedarone on the Action Potential of Rabbit Atrial Muscle Preparations: Comparison With Amiodarone

Abstract: Dronedarone, a noniodinated derivative of amiodarone, is under evaluation as a potentially less toxic anti-arrhythmic alternative to amiodarone. The acute and chronic electrophysiologic effects of dronedarone and amiodarone were compared in isolated rabbit atrial muscle by microelectrode techniques. Four-week PO treatment with dronedarone or amiodarone increased action potential duration (APD90) (58 +/- 4 ms control versus 69 +/- 2 ms dronedarone, p < 0.01; 68 +/- 3 ms amiodarone, p < 0.01 for a 100-mg/kg/d do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 34 publications
0
73
1
Order By: Relevance
“…The most consistent effect is usedependent inhibition of maximum upstroke velocity, both after acute and sustained administration. Acute administration of 0.1 to 10 mol/L of dronedarone decreased action potential duration in rabbit papillary muscle, 22 rabbit atrial muscle, 37 and the canine papillary muscle preparation, 25 with no effect on guinea pig ventricular myocytes. 24 On the other hand, sustained administration of drug increased action potential duration in rabbit papillary muscles 22 and rabbit atrial muscles.…”
Section: Electrophysiological Properties Of Dronedarone In Vitro Expementioning
confidence: 91%
See 1 more Smart Citation
“…The most consistent effect is usedependent inhibition of maximum upstroke velocity, both after acute and sustained administration. Acute administration of 0.1 to 10 mol/L of dronedarone decreased action potential duration in rabbit papillary muscle, 22 rabbit atrial muscle, 37 and the canine papillary muscle preparation, 25 with no effect on guinea pig ventricular myocytes. 24 On the other hand, sustained administration of drug increased action potential duration in rabbit papillary muscles 22 and rabbit atrial muscles.…”
Section: Electrophysiological Properties Of Dronedarone In Vitro Expementioning
confidence: 91%
“…24 On the other hand, sustained administration of drug increased action potential duration in rabbit papillary muscles 22 and rabbit atrial muscles. 37 The action potential duration of dog papillary muscle remained unchanged. 25 In canine left ventricular Purkinje fibers, 10 mol/L of dronedarone reduced the incidence of early and delayed afterdepolarizations evoked by dofetilide and ouabain, respectively.…”
Section: Electrophysiological Properties Of Dronedarone In Vitro Expementioning
confidence: 97%
“…32 It was also found that dronedarone produced less prolongation of ventricular repolarization than amiodarone during long-term treatment of canines. The lack of APD prolongation with short term administration in animal models may relate to the balanced influence on depolarizing and repolarizing currents.…”
Section: Evidence From Animal Studiesmentioning
confidence: 96%
“…46 Dronedarone is a benzofuran derivative with an electropharmacologic profile resembling that of amiodarone but with different relative effects on individual ion channels. [47][48][49][50] The structural changes made to amiodarone to produce dronedarone include the removal of iodine and the addition of a methane-sulfonyl group.…”
Section: Ranolazine+drondedaronementioning
confidence: 99%